2010 8th International Pipeline Conference, Volume 4 2010
DOI: 10.1115/ipc2010-31397
|View full text |Cite
|
Sign up to set email alerts
|

End Boundary Effects on Local Buckling Response of High Strength Linepipe

Abstract: In this paper, the significance of the length to diameter ratio (L/D) on the local buckling response was evaluated using continuum finite element modelling procedures. A numerical model was developed, using the finite-element simulator ABAQUS/Standard, to predict the local buckling and post-buckling response of high strength pipelines subject to combined state of loading. The numerical procedures were calibrated using test data from large-scale experiments examining the local buckling of high strength linepipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Numerical modeling investigations, have indicated pipe segment lengths greater than 10 diameters would be sufficient to mitigate the end boundary conditions and mechanical response of an over-constrained system [12]. Other recent physical experiments and numerical simulations support this argument and have examined pipe segment lengths of 5 to 20 pipe diameters at [6,15,17].…”
Section: Boundary Conditionsmentioning
confidence: 88%
See 4 more Smart Citations
“…Numerical modeling investigations, have indicated pipe segment lengths greater than 10 diameters would be sufficient to mitigate the end boundary conditions and mechanical response of an over-constrained system [12]. Other recent physical experiments and numerical simulations support this argument and have examined pipe segment lengths of 5 to 20 pipe diameters at [6,15,17].…”
Section: Boundary Conditionsmentioning
confidence: 88%
“…Characteristics of the stress-strain relationship through the subyield plastic and transition regimes may be one of the factors accounting for the apparent dependency of compressive strain capacity on material grade and yield strength [4]. Studies conducted by the authors [12,13,15,19] have observed a relationship between peak moment (i.e. strength capacity) and material grade but not with compressive strain capacity (i.e.…”
Section: Y/t Ratiomentioning
confidence: 96%
See 3 more Smart Citations